Government Involvement in Corporate Debt Restructuring : Case Studies from the Great Recession - Grigorian, David (IMF Working Papers; Working Paper ;, 2010)
The paper examines recent episodes of government involvement in corporate debt restructurings. It argues that corporate debt restructuring is an important step toward recovery from a financial crisis. We then discuss the rationale for, and modalities of, the state intervention in corporate debt workouts through reviewing six countries with large scale corporate debt workouts. Case studies reveal that the costs of corporate sector rescue are significant and in several cases on par with the costs of financial sector bailouts. The paper sheds light on the importance of contingent liabilities and associated risks to government balance sheet from the corporate debt side and emphasizes the need for improved contingency planning for corporations with potential systemic impact.